Analisis Kesenjangan Literasi Digital Masyarakat dalam Mengakses dan Memahami Kampanye Politik Daring pada Pilkada Bantul 2020 - Khalifa Nur Khaliq Pohan; Kanina Aufia; Bunga Indriani Azzahra; Firman (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The purpose of this study is to examine the differences in digital literacy of the community during the 2020 Bantul Pilkada campaign. Political campaigns have undergone significant transformations during the COVID-19 pandemic with increased use of digital technology and social media. However, gaps in knowledge and access to technology affect community participation in politics. This case study investigates how the digital divide affects the efficiency of political campaigns in Bantul, especially in terms of reaching voters with limited internet access. In addition, social media such as Facebook, Instagram, and WhatsApp are effective campaign tools for reaching younger voters, but are less effective in reaching groups of people who are less digitally literate. To bridge the digital divide and encourage more inclusive political participation in the future, this study suggests efforts to improve digital infrastructure and technological literacy.